INFLUENCE OF THE POLYMORPHIC MARKER T-786C OF THE ENOS3 GENE IN DIABETIC NEPHROPATHY - Jabbarov O. O; Sapayeva Z. A (Galaxy International Interdisciplinary Research Journal, 2021)
This article presents the results of a study of 129 patients with type 2 diabetes and 110 healthy people to determine whether polymorphic T-786C markers of the ENOS3 gene are associated with the development of diabetic nephropathy. Patients in the main group: 65 patients with a disease duration of up to 10 years, without diabetic nephropathy (33 patients) and with diabetic nephropathy (32 patients), 64 patients with diabetes lasting more than 10-20 years, with no diabetic nephropathy (31 patients ) and diabetic nephropathy (33 patients). Genotyping was carried out by polymerase chain reaction. The study showed the association of the C allele and the СС genotype of the ENOS3 gene with a risk of developing diabetic nephropathy in patients with type 2 diabetes mellitus in the studied Uzbek nation.